PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Yunita, Erna; Laspita, Romi; Arsilestari, Putri; Indriyanto; Syahrul Rizal, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of critical thinking skills among fifth-grade students in learning Natural and Social Sciences (IPAS). One effort to address this problem is through the implementation of the Problem Based Learning (PBL) model. This study aims to describe the improvement of students’ critical thinking skills through the application of the Problem Based Learning model in class V Ibnu Firnas of SD Islam Terpadu Al Fikri Pekanbaru.The research method used was Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of two meetings and four stages, namely planning, action implementation, observation, and reflection. The research was carried out in the even semester of the 2025/2026 academic year. The research subjects were 28 fifth-grade students, consisting of 15 male students and 13 female students. Data collection techniques included observation, tests, and documentation.The results of the study showed an improvement in students’ critical thinking skills in each cycle. In Cycle I, 12 students (43%) achieved the mastery category. In Cycle II, the number of students who achieved mastery increased to 23 students (82%). Based on these findings, it can be concluded that the application of the Problem Based Learning (PBL) model can improve the critical thinking skills of fifth-grade students at SD Islam Terpadu Al Fikri Pekanbaru.